Spatial Spillover Impact of Sectoral Government Expenditure on Poverty Alleviation in South Kalimantan Province - NovitasariMega; Aditya IskandarDoddy (The Journal of Indonesia Sustainable Development Planning, 2022)
Poverty is still one of the forefront issues in developing countries. It could hamper the achievement of sustainable development goals, thereby triggering a recurring call on the government’s role in mitigating poverty. This paper contributed to the debate on the role of sectoral government spending under the fiscal decentralization policy to combat poverty. Using a case study in South Kalimantan Province, we employed a spatial panel data analysis covering 13 districts from 2010-2020. This study investigated the presence of spatial dependency on poverty and the spatial spillover impact of government expenditure— education, health, housing, public facilities, and social protection—on poverty. The research found the existence of spatial autocorrelation on poverty and the significant high-cluster poverty in the agriculture- based region. The direct estimation from the Spatial Durbin Model uncovered that government expenditure on education, health, and social protection significantly alleviated poverty, while housing and public facilities expenditure remained insignificant in reducing the poverty rate. Besides, education spending also has a significant indirect effect on poverty, indicating the spatial spillover impact of education spending by the neighbors on poverty in a region.